Responding to climate change in the design of the urban river landscape - Toroitich, Caleb (School of Architecture, Planning and Geomatics, 2014)
Two main challenges facing humanity today are sustainable development and avoidance of human-induced climate change. In many ways these two threaten human civilisation and development and the very existence of life on earth. These words are mentioned in UN conferences; in professional bodies' workshops; in the corridors of government departments; in school classrooms and among the general public. There is also extensive amount of literature on the same subjects. Many recognise the problems and try to look for solutions. Climate change has impacted negatively on both rural and urban landscapes. River corridors uniquely cross through many environments and ideally should exhibit same character wherever it crosses irrespective of adjoining land uses. However. where it crosses urban landscapes, places of intense and varied land uses, human interference and abuse is most witnessed and recognisable. As more and more people migrate to urban areas, the situation is bound to get worse. New ways of planning and design of this landscape, especially in the face of adverse effects of climate change, should be sought. This dissertation seeks to be part of this endeavour to propose methods of how the urban river landscape can or should be moulded to reduce the impact of climate change first on its ecological integrity and balance and secondly to its socio-economic and cultural aspects to urban dwellers.